DETERMINING THE DE-DIESELISATION PRIORITIES OF DISTRIBUTED DIESEL GENERATORS IN AN ELECTRICITY COMPANY - Nurdianto, Kresna; Kusumastuti, Ratih Dyah (Journal of Environmental Science and Sustainable Development, 2024)
The Indonesian Electricity Company (PLN) is one of the main players in the energy transition in Indonesia, and the company plans to achieve net zero emissions by 2060. One way to do this is by implementing the de-dieselisation program, i.e. reducing the use of diesel power plants (PLTD) with new energy and renewable power plants. The Indonesian electricity supply business plan (RUPTL) 2021-2030 targets the reduction of electricity supply from PLTD by 87% by 2030. The program requires a method to determine the order of priorities of PLTDs to be de-dieselised. This research uses multicriteria decision making, namely, analytical hierarchy process (AHP) and technique for order preference by similarity to ideal solutions (TOPSIS) to develop a prioritisation methods and determine the rank of priorities of 22 PLTDs Sumatra island that will undergo de-dieselisation. The criteria are identified from the literature and confirmed with four experts from the company. The criteria are categorised into security of supply, costs, and environmental factors. AHP is then used to calculate the weight of all criteria and sub-criteria, while TOPSIS is used to determine the rank. The results show that the affordability criterion is the most critical factor (0.535), followed by the security of supply (0.312) and environmental factors (0.153). The results also show that PLTD A18, A14 and A7 are the top three PLTDs prioritised for de-dieselisation because they provide the closest distance to the ideal criteria. This research contributes by providing reference in selecting the PLTD that will be selected for de-dieselisation program.